2019
DOI: 10.1186/s12884-019-2596-9
|View full text |Cite
|
Sign up to set email alerts
|

Maternal characteristics and outcomes affected by hypothyroidism during pregnancy (maternal hypothyroidism on pregnancy outcomes, MHPO-1)

Abstract: Background: Hypothyroidism in pregnancy is an arena of ongoing research, with international conflicts regarding screening, management, and outcomes. Various studies have described the outcomes depending on geographical and international diagnostic criteria. No study has been conducted in this regard from the region of Pakistan. Therefore, we aim to report the clinical features and maternal outcomes of hypothyroid pregnancies and compare the maternal outcomes between uncontrolled and controlled TSH levels in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 48 publications
4
31
0
7
Order By: Relevance
“…Although the mechanism involved is not clear, three possible explanations for the association of TAI with miscarriage have been proposed: (1) Pregnancy loss is an epiphenomenon and not a direct effect of TAI-the presence of TAI reflects a generalized activation of the immune system and specifically represents an increased reactivity against the fetusplacental unit [11]; (2) The presence of TAI may act as a factor of infertility and may delay conception; therefore, when women with TAI become pregnant, they have an increased risk of miscarriage due to advanced age [12][13][14]; 3The loss of pregnancy may be secondary to a deficiency in thyroid hormone levels or a lower ability of the thyroid to adapt appropriately to pregnancy demands [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism involved is not clear, three possible explanations for the association of TAI with miscarriage have been proposed: (1) Pregnancy loss is an epiphenomenon and not a direct effect of TAI-the presence of TAI reflects a generalized activation of the immune system and specifically represents an increased reactivity against the fetusplacental unit [11]; (2) The presence of TAI may act as a factor of infertility and may delay conception; therefore, when women with TAI become pregnant, they have an increased risk of miscarriage due to advanced age [12][13][14]; 3The loss of pregnancy may be secondary to a deficiency in thyroid hormone levels or a lower ability of the thyroid to adapt appropriately to pregnancy demands [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The proper functioning of the thyroid axis is essential for the normal development of the nervous system, especially in the first trimester of gestation when fetal thyroid hormone concentration depends directly on the maternal hormonal contribution. Pregnant women with hypothyroidism are at a higher risk of suffering from preeclampsia, placental abruption, and postpartum hemorrhage, among others [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The number and combination of symptoms and signs may indicate a relationship with the diagnosis and treatment of hypothyroidism. Previous studies found a higher rate of 20–40% positive antibodies in hypothyroid pregnancy [ 94 , 96 , 97 ]. Despite the low rate of positive antibodies, new Mexican studies should be conduct for comparison.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, this is the first application of cluster analysis to identify distinct risk factors and demographic features in a cohort of first-trimester pregnant women with a thyroid profile, a disorder believed to involve multiple disease subtypes [ 87 , 88 , 89 , 90 , 91 ]. Several previous studies analyzed the clinically relevant features and maternal outcomes of hypothyroid and euthyroid pregnancy, leading to new insights about the classification of women with similar patterns [ 92 , 93 , 94 ]. While the impact of these studies contributes to the literature, none of them focus on first trimester pregnancy or risk factor of thyroid pathology.…”
Section: Discussionmentioning
confidence: 99%